2019
DOI: 10.17765/2176-9168.2019v12n4p1251-1266
|View full text |Cite
|
Sign up to set email alerts
|

Suscetibilidade Ao Entupimento De Gotejadores Aplicando Água Residuária Doméstica Tratada

Abstract: Objetivou-se com este trabalho analisar as alterações do desempenho hidráulico de distintos modelos de gotejadores que operaram com água residuária doméstica tratada, bem como obter modelos empíricos em função da variável tempo de operação e qualidade do efluente. Para isso, montou-se um experimento na Universidade Federal Rural do Semi-Árido (UFERSA) composto por quatro unidades de irrigação, dotadas de três tipos de gotejadores (Plastro Hydrodrip Super, Netafim Tiran e Netafim PCJ-CNJ), em três repetições (t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 9 publications
(11 reference statements)
1
4
0
2
Order By: Relevance
“…data of FCV and T in treatments D1 and D2, while the linear and quadratic models were best fit for treatments D3 and D4 and treatment D5, respectively. These results differ from Costa et al (2019), where the square root model was the one that best fit the FCV and T data of a 1.65 Lh -1 in non-self-compensating emitter operating with sanitary wastewater for 400 h. Table 3 also shows that the adjusted regression models presented a coefficient of determination (R 2 ) greater than or equal to 80%, which is more reliable for predictive purposes according to Olmez (2009).…”
Section: Regression Of Flow Rate Variation Coefficient (Fcv)mentioning
confidence: 61%
See 2 more Smart Citations
“…data of FCV and T in treatments D1 and D2, while the linear and quadratic models were best fit for treatments D3 and D4 and treatment D5, respectively. These results differ from Costa et al (2019), where the square root model was the one that best fit the FCV and T data of a 1.65 Lh -1 in non-self-compensating emitter operating with sanitary wastewater for 400 h. Table 3 also shows that the adjusted regression models presented a coefficient of determination (R 2 ) greater than or equal to 80%, which is more reliable for predictive purposes according to Olmez (2009).…”
Section: Regression Of Flow Rate Variation Coefficient (Fcv)mentioning
confidence: 61%
“…Figure 2 shows the flow rate variation coefficient (FCV) values of the drip units equipped with three types of non-selfcompensating emitters applying dilutions of water produced during 160 h. The FCV is a hydraulic performance indicator that detects the obstruction of emitters when its value increases over the time of operation and its classification changes from good (FCV ≤ 10%) to reasonable (10%> FCV ≤ 20%) or unacceptable (FCV > 20%) (Asabe, 2008;Costa et al, 2019). It was also found that D5 was the treatment that most influenced the increase in FCV, and consequently, the obstruction of the emitters over the operation time of the irrigation units.…”
Section: Flow Rate Coefficient Of Variation (Fcv) Behavior Of Non-selfcompensating Drippers Applied Dilutions Of Treated Water Produced Bmentioning
confidence: 99%
See 1 more Smart Citation
“…Geralmente, a obstrução altera a vazão dos gotejadores e, consequentemente, diminui a uniformidade de aplicação de água e a eficiência dos sistemas de irrigação localizada (DAZHUANG et al, 2009;DURAN-ROS et al, 2009). Comparando situação experimental semelhante, Costa et al (2019) constatou redução significativa nos valores da Q do gotejador G1 (1,65 L h -1 ) não autocompensante de 6,01% na unidade gotejadora abastecida com percolado de aterro sanitário diluído e submetida à pressão de 140 kPa. Silva et al (2014) ao trabalharem com unidades gotejadoras aplicando água residuária tratada da indústria da castanha de caju sob pressões de serviço, notou-se que após 160 h de operação não é recomendada o uso de gotejadores de baixa vazão nominal (≤ 1,6 L h -1 ) e maior comprimento de labirinto (≥ 58 mm).…”
Section: Resultsunclassified
“…A irrigação localizada se destaca para aplicação de águas residuárias pela elevada eficiência de aplicação do efluente, minimização do escoamento superficial e da percolação, redução dos teores de sais próximo ao sistema radicular das plantas e prevenção da formação de aerossóis (HERMES et al, 2020). No entanto, a grande vulnerabilidade da aplicação de águas residuárias pela irrigação localizada, consiste na alta suscetibilidade ao entupimento dos gotejadores em função do nível de tratamento do efluente (COSTA et al, 2019) e das características internas dos emissores (BATISTA et al, 2018).…”
Section: Introductionunclassified